The Market and Wider Benefits of Higher Education to Individuals and Society of the Educational System in Iran - Rouhollah Bagherimajd; Mir Seyed Abbaszadeh; Mohammad Hasani; Yadollah Mehralizadeh; Ebrhim Salehi Omran (توسعه اجتماعی)
The purpose of this study was to analyze the interaction between the market and wider benefits of higher education to individuals and society of the educational system in Iran. The method used in this study was correlational. Statistical population used in this survey faculty 5 universities of the country and based on a stratified random sample of 263 peopel were selected. Research questionnaire was the based on a combination of indicators of general policy documents and the model of business London (2013), Validity and reliability was suitable. Analysis method, was, structural equation with Using PLS software. The results indicate a significant, direct and positive effect on the non-market-individual, non-market-social and market-social by market-individual. The market-social on non-market-social and non-market-individual has a direct effect. on the other hand, the market-individual on non-market-social and non-market-individual has a indirect effect.